2017
DOI: 10.1074/mcp.m116.058172
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Chromatographic Strategy for Multiplexing In Parallel Reaction Monitoring Mass Spectrometry: Insights from Quantitation of Activated Kinases

Abstract: Kinases are involved in the regulation of most cellular processes and are implicated in numerous human disease states. Five hundred and eighteen human kinases are known, and between 200 and 400 are typically expressed in a given cell type (1-3). Quantitative measurement of kinase activity is of critical importance in numerous biological applications, including studies of cellular signaling, cancer biomarker discovery, and drug development. An ideal strategy for functional kinase analysis must combine an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…A second strategy is to design orthogonal sulfonyl-fluoride-based probes based on distinct kinase-recognition scaffolds. Finally, future efforts will seek to improve the sensitivity of kinase quantitation through advanced instrumentation and proteomic methods, 30 including the use of parallel reaction monitoring.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…A second strategy is to design orthogonal sulfonyl-fluoride-based probes based on distinct kinase-recognition scaffolds. Finally, future efforts will seek to improve the sensitivity of kinase quantitation through advanced instrumentation and proteomic methods, 30 including the use of parallel reaction monitoring.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Thus, novel biomarkers of interest can be easily added. This multiplexing opportunity allows for the quantification of up to a few hundred analytes in a single run [22,31,[48][49][50], whereas ELISA is limited to one biomarker that can be analyzed at one time. Albeit, it is possible to develop multiplexed ELISAs, that is, multiplexed bead array assays (MBAA), but their development is very expensive, time-consuming, and complex [51], and again requires specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…the Q Exactive quadrupole-Orbitrap) and does not require preselection of fragment ions, has shown promise in decreasing both assay development time and cost while maintaining high sensitivity. 133135 For example, Lawrence and colleagues introduced a method to mine a large database of previous LC-MS analyses to assist with phosphopeptide selection and retention time scheduling; interestingly, for a set of 101 peptides, their “plug and play” PRM approach outperformed both DDA and DIA strategies in reproducibility and number of peptides identified. 136 Urisman et al .…”
Section: Targeted Lc-ms and Determination Of Phosphorylation Stoichiomentioning
confidence: 99%
“…recently demonstrated that label-free PRM multiplexing could be expanded to quantify over 800 peptides from 150 kinases in a single analysis using the separation capabilities of a long monolithic silica-C18 capillary column. 133 Spiked in stable isotope labeled standards can also be used to trigger analysis of the corresponding endogenous peptide, thus optimizing data acquisition time and augmenting multiplexing capabilities. 137 An interesting twist on IS-PRM incorporates TMTzero labeling of the standard trigger peptides and TMT 10plex labeling of samples to generate a targeted analysis that is multiplexed in both target peptide number and sample number.…”
Section: Targeted Lc-ms and Determination Of Phosphorylation Stoichiomentioning
confidence: 99%